Investigation into the misincorporation of norleucine into a recombinant protein vaccine candidate. (1st June 2015) - Ni, Joyce; Gao, Meg; James, Andrew; Yao, Jiansheng; Yuan, Tao; Carpick, Bruce; D'Amore, Tony; Farrell, Patrick
Abstract: A high level of norleucine misincorporation was detected in a recombinant methionine-rich protein vaccine candidate expressed in E. coli K12. An investigation was conducted to evaluate a simple remediation strategy to reduce norleucine misincorporation and to determine if the phenomenon was either (a) due to the depletion of methionine during fermentation, (b) a result of the cultivation environment, or (c) a strain-specific effect. While supplementation with exogenous methionine improved product quality, the undesirable biosynthesis of non-standard amino acids such as norleucine and norvaline persisted. In contrast, non-standard amino acid biosynthesis was quickly minimized upon selection of an appropriate fed-batch process control strategy, fermentation medium, and nutrient feed. By expressing the same protein in E. coli BL21(DE3), it was determined that the biosynthesis of norleucine and norvaline, and the misincorporation of norleucine into the protein were primarily attributed to the use of E. coli K12 as the host for protein expression.